The Expression of Hospitality in the revered works of Uzbek heritage - Erkaboyeva, Nargiza (The Lingua Spectrum, 2025)
This article explores the concept of hospitality in the Uzbek language and its reflection in the historical and cultural heritage of the Uzbek people. Hospitality has been highly valued in our people’s centuries-old historical and cultural traditions, becoming an integral part of our national culture. By welcoming guests and showing them respect, our people demonstrate their tolerance, sincerity, and nobility. Although Hospitality plays a significant role in our culture, it hasn’t been investigated sufficiently from the linguistic point of view. It examines how hospitality is expressed in everyday communication and how it is portrayed in sacred books such as the Holy Qur’an and the Hadiths of the Prophet Muhammad, as well as in classical literary works like “Qutadgu Bilig,” “Qobusnoma,” and “Mahbub ul-Qulub.” Various examples of sayings, phrases, and social norms related to hospitality as depicted in these revered sources will be presented in this article. The values of Hospitality will be discussed in this article as well.